Incidences and outcomes of intra-operative vs. postoperative paediatric cardiac arrest: A retrospective cohort study of 42 776 anaesthetics in children who underwent noncardiac surgery in a Thai tertiary care hospital - Rattana-Arpa S. (2023)
BACKGROUNDThe reported incidence of paediatric perioperative cardiac arrest (PPOCA) in most developing countries ranges from 2.7 to 22.9 per 10 000 anaesthetics, resulting in mortality rates of 2.0 to 10.7 per 10 000 anaesthetics. The definitions of 'peri-operative' cardiac arrest often include the intra-operative period and extends from 60 min to 48 h after anaesthesia completion. However, the characteristics of cardiac arrests, care settings, and resuscitation quality may differ between intra-operative and early postoperative cardiac arrests.OBJECTIVETo compare the mortality rates between intraoperative and early postoperative cardiac arrests (<24 h) following anaesthesia for paediatric noncardiac surgery.DESIGNA retrospective cohort study.SETTINGIn a tertiary care centre in Thailand during 2014 to 2019, the peri-operative period was defined as from the beginning of anaesthesia care until 24 h after anaesthesia completion.PATIENTSPaediatric patients aged 0 to 17 years who underwent anaesthesia for noncardiac surgery.MAIN OUTCOME MEASURESMortality rates.RESULTSA total of 42 776 anaesthetics were identified, with 63 PPOCAs and 23 deaths (36.5%). The incidence (95% confidence interval) of PPOCAs and mortality were 14.7 (11.5 to 18.8) and 5.4 (3.6 to 8.1) per 10 000 anaesthetics, respectively. Among 63 PPOCAs, 41 (65%) and 22 (35%) occurred during the intra-operative and postoperative periods, respectively. The median [min to max] time of postoperative cardiac arrest was 3.84 [0.05 to 19.47] h after anaesthesia completion. Mortalities (mortality rate) of postoperative cardiac arrest were significantly higher than that of intra-operative cardiac arrest at 14 (63.6%) vs. 9 (22.0%, P = 0.001). Multivariate analysis of risk factors for mortality included emergency status and duration of cardiopulmonary resuscitation with adjusted odds ratio 5.388 (95% confidence interval (1.031 to 28.160) and 1.067 (1.016 to 1.120).CONCLUSIONSPostoperative cardiac arrest resulted in a higher mortality rate than intra-operative cardiac arrest. A high level of care should be provided for at least 24 h after the completion of anaesthesia.TRIAL REGISTRATIONNone.CLINICAL TRIAL NUMBER AND REGISTRY URLNA.